Novel narkers of recovery from overtraining syndrome: The EROS-LONGITUDINAL study - Cadegiani, F. A.; Silva, P. H. L.; Abrao, T. C. P.; Kater, C. E. (International Journal of Sports Physiology and Performance, 2021)
Purposes: Overtraining syndrome (OTS) is an unexplained underperformance syndrome triggered by excessive training, insufficient caloric intake, inadequate sleep, and excessive cognitive and social demands. Investigation of the recovery process from OTS has not been reported to date. The objective was to unveil novel markers and biochemical and clinical behaviors during the restoration process of OTS.